2020
DOI: 10.1111/ppc.12660
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem and sexual quality of life among obese women

Abstract: Purpose: To evaluate the sexual quality of life and self-esteem of obese women and the relationship between them.Design and Methods: This is a descriptive and cross-sectional study. A descriptive questionnaire, Rosenberg Self-Esteem Scale, and Sexual Quality of Life Questionnaire were used to collect the data. Findings: Participants had a moderate level of self-esteem. The mean scores of the participants were 50.45 + 10.23 for Sexual Quality of Life Questionnaire. A positive correlation was found between self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Türkben et al (2021) had found that sexual QoL has a positive correlation with self-esteem. 52 Self-esteem, as a positive psychological state, affects not just an individual’s QoL but also that of their partners, as demonstrated in a study by Ha et al (2020) which found that positive psychological characteristics have actor and partner effects on couples with infertility. 53 Furthermore, people with higher self-esteem have better social acceptability and interpersonal relationships.…”
Section: Discussionmentioning
confidence: 97%
“…Türkben et al (2021) had found that sexual QoL has a positive correlation with self-esteem. 52 Self-esteem, as a positive psychological state, affects not just an individual’s QoL but also that of their partners, as demonstrated in a study by Ha et al (2020) which found that positive psychological characteristics have actor and partner effects on couples with infertility. 53 Furthermore, people with higher self-esteem have better social acceptability and interpersonal relationships.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between women's education level and quality of sexual life was evaluated in all the selected studies. A statistically significant relationship was observed between education and quality of sexual life in four studies (13,14,17,21), while no significant relationship was observed between these two variables in five other studies (15,16,(18)(19)(20).…”
Section: Key Messagesmentioning
confidence: 82%
“…Among the included studies, eight studies were crosssectional (13)(14)(15)(16)(17)(18)(19)(20) and one study was case-control (21). Of the mentioned studies, four cases had been conducted in Iran, four in Turkey, and one in South Korea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common physical change that affects body image during pregnancy is weight gain. In a study conducted with obese women, it was determined that as the body mass index increased, the quality of sexual life decreased and sexual dysfunctions increased (Türkben & Kaplan, 2020). Similar results were found in the studies conducted with pregnant women.…”
Section: Discussionmentioning
confidence: 99%